Preparation method of carbon-coated porous tin
Through the preparation method of carbon-coated porous tin, the powdering and crushing problems caused by volume expansion of tin-based anode materials are solved, the electrochemical reaction efficiency and cycle stability are improved, and the environmental friendliness and recyclability are achieved. .
Patent Information
- Application Number
- CN202411315482.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
Smart Images

Figure CN119187558A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion battery negative electrode preparation, and in particular relates to a method for preparing carbon-coated porous tin. Background Art
[0002] Compared with lithium-ion batteries, sodium-ion batteries have the advantages of low cost and abundant reserves, which make them a new type of secondary battery technology that can be commercialized on a large scale. However, due to the radius of sodium ions, Larger than the radius of lithium ions This makes graphite materials unsuitable for use as negative electrodes in sodium-ion batteries. Typical negative electrode materials for sodium-ion batteries are hard carbon materials, but the low compaction density of hard carbon materials is contrary to the development trend of high-energy-density battery cells. Therefore, the development of high-energy-density negative electrode materials for sodium-ion batteries is a necessary condition for achieving their large-scale commercialization.
[0003] Tin-based materials have been widely studied as anodes for sodium-ion batteries due to their high capacity, abundant resources, and environmental friendliness. They boast a high specific capacity of up to 847 mAh / g and a low potential (-0.2 V vs. Na / Na+). However, unlike intercalation-type anode materials, tin-based materials undergo alloying reactions during sodium insertion, resulting in a volume change exceeding 400%. This significant volume expansion causes them to gradually fragment and pulverize, ultimately losing connection with the current collector. Furthermore, tin-based anodes can self-aggregate during cycling, exacerbating the volume expansion effect and extending the distance for sodium ion transport.
[0004] To address these issues, current methods for improving tin-based negative electrode materials can be categorized as controlling the process, constructing special-shaped structures, and composite materials, but the effects need to be improved. To this end, we propose a method for preparing carbon-coated porous tin. Summary of the Invention
[0005] The purpose of the present invention is to provide a method for preparing carbon-coated porous tin. The three-dimensional porous material provided can prevent the material from pulverizing and breaking due to volume expansion. At the same time, the present invention isolates the tin through coating, thereby enhancing the structural stability of the porous tin and preventing material contact and self-aggregation. The three-dimensional porous structure of the porous tin gives it a higher specific surface area and a larger contact area with the electrolyte, thereby improving the efficiency of the electrochemical reaction. The carbon coating can enhance the cyclic stability of the porous tin and enhance the reliability and durability of the material. Compared with hard carbon, tin is more environmentally friendly and recyclable. It helps to reduce the environmental burden. By adding high-melting-point metals to form an alloy, the melting and deformation of the tin during the coating process is avoided.
[0006] The technical solutions adopted by the present invention are as follows:
[0007] A method for preparing carbon-coated porous tin comprises preparing an alloy by a gas atomization method, then removing an auxiliary metal from the alloy to prepare the porous tin, and finally achieving doping and separating the porous tin by a hard carbon coating method to complete the preparation of the carbon-coated porous tin.
[0008] Preferably, the preparation of the carbon-coated porous tin comprises the following specific steps:
[0009] Step 1: Alloy smelting: The alloy is melted and mixed to obtain a uniform alloy liquid;
[0010] Step 2: Granulation: The molten alloy is made into alloy particles in an atomizing tank by gas atomization;
[0011] Step 3: Etching: removing at least one auxiliary metal in the alloy by etching to obtain porous tin or tin alloy;
[0012] Step 4: Coating: The porous tin is surface treated by a coating method to achieve doping and separation of the porous tin.
[0013] Preferably, in step 1, the alloy contains tin and at least one other auxiliary metal; the tin content is 80%-99%, and the auxiliary metal is one or more of antimony, germanium, copper, manganese, iron, cobalt, nickel, aluminum, silver, zinc, and tungsten; and the purity of the raw metal is greater than or equal to 99.99%.
[0014] Further preferably, in step 1: the smelting temperature is higher than the melting point of the alloy; the smelting protective atmosphere is hydrogen and one or more of helium, argon, and nitrogen; the purity of a single gas is greater than 99.99%, and the proportion of hydrogen is less than or equal to 2%.
[0015] Preferably, in step 2, the atomizing gas is hydrogen and one or more of helium, argon, and nitrogen; the purity of the single gas is greater than 99.99%, and the proportion of hydrogen is less than or equal to 2%; the atomizing pressure is 1 MPa-10 MPa; and the median particle size D50 of the alloy material is 0.2-10 μm.
[0016] Preferably, step 3 is to remove at least one auxiliary metal in the alloy by one or more of acid, alkali or ion beam etching, sputter etching, plasma etching, laser etching, electrochemical etching, and sandblasting etching methods to obtain porous tin or tin alloy.
[0017] Further preferably, when the etching method adopts acid or alkali etching, the acid is one or more strong acid solutions, such as hydrochloric acid, sulfuric acid or nitric acid; the alkali is one or more concentrated strong alkali solutions, such as concentrated sodium hydroxide solution or concentrated potassium hydroxide solution.
[0018] Preferably, in step 4, the coating method is chemical vapor deposition (CVD) or polymer coating-carbonization.
[0019] Further preferably, in step 4, when chemical vapor deposition (CVD) is used for coating, the carbon source of the chemical vapor deposition (CVD) method is one or more of methane, ethylene, ethane, and acetylene gases; the carrier gas is one or more of inert gases, such as helium or argon; and the reaction temperature is lower than the melting point of porous tin.
[0020] The technical effects achieved by the present invention are:
[0021] 1. In the present invention, the three-dimensional porous material provided can prevent the material from pulverizing and breaking due to volume expansion; at the same time, the present invention isolates the tin by coating, thereby enhancing the structural stability of the porous tin and preventing material contact and self-aggregation.
[0022] 2. In the present invention, the three-dimensional porous structure of porous tin gives it a higher specific surface area and a larger contact area with the electrolyte, thereby improving the efficiency of the electrochemical reaction.
[0023] 3. In the present invention, carbon coating can enhance the cycle stability of porous tin and improve the reliability and durability of the material.
[0024] 4. In the present invention, tin is more environmentally friendly and recyclable than hard carbon, which helps reduce the environmental burden.
[0025] 5. In the present invention, by adding high melting point metal to form an alloy, the melting and deformation of tin during the coating process is avoided. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The present invention is a flow chart of a method for preparing carbon-coated porous tin. DETAILED DESCRIPTION
[0027] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is described in detail below with reference to the following examples. It should be understood that the following text is only used to describe one or more specific embodiments of the present invention and does not strictly limit the scope of protection of the present invention.
[0028] Example 1:
[0029] like Figure 1 As shown, a method for preparing carbon-coated porous tin is provided, wherein an alloy is prepared by a gas atomization method, and then porous tin is prepared by removing the auxiliary metal in the alloy, and finally doping and separation of the porous tin are achieved by a hard carbon coating method to complete the preparation of carbon-coated porous tin.
[0030] Specifically, the preparation of carbon-coated porous tin includes the following specific steps:
[0031] Step 1: Alloy smelting: The alloy is melted and mixed to obtain a uniform alloy liquid;
[0032] Wherein, in step 1, the alloy contains tin and at least one other auxiliary metal; the tin content is 80%-99%, and the auxiliary metal is one or more of antimony, germanium, copper, manganese, iron, cobalt, nickel, aluminum, silver, zinc, and tungsten; the purity of the raw metal is greater than or equal to 99.99%; further, in step 1: the smelting temperature is higher than the melting point of the alloy; the smelting protective atmosphere is hydrogen and one or more of helium, argon, and nitrogen; the purity of a single gas is greater than 99.99%, and the proportion of hydrogen is less than or equal to 2%; it should be noted here that the smelting protective atmosphere used is a mixture of one or more of hydrogen and other gases, but the proportion of hydrogen is less than or equal to 2%, for example, 2% hydrogen and 98% helium, or 1.5% hydrogen and 98.5% nitrogen, or 2% hydrogen, 60% helium and 38% nitrogen;
[0033] Step 2: Granulation: The molten alloy is made into alloy particles in an atomizing tank by gas atomization;
[0034] In step 2, the atomizing gas is hydrogen and one or more of helium, argon, and nitrogen; the purity of a single gas is greater than 99.99%, and the proportion of hydrogen is less than or equal to 2%; it should be noted here that the atomizing gas used is a mixture of one or more of hydrogen and other gases, but the proportion of hydrogen is less than or equal to 2%, for example, 2% hydrogen and 98% helium, or 1.5% hydrogen and 98.5% nitrogen, or 2% hydrogen, 60% helium and 38% nitrogen; the atomizing pressure is 1 MPa-10 MPa; the median particle size D50 of the alloy material is 0.2-10 μm.
[0035] Step 3: Etching: removing at least one auxiliary metal in the alloy by etching to obtain porous tin or tin alloy;
[0036] Among them, step 3 specifically involves removing at least one auxiliary metal in the alloy by one or more of acid, alkali or ion beam etching, sputter etching, plasma etching, laser etching, electrochemical etching, and sandblasting etching methods to obtain porous tin or tin alloy; further, when the etching method adopts acid or alkali etching; the acid is one or more strong acid solutions; specifically, hydrochloric acid, sulfuric acid or nitric acid; the alkali is one or more strong alkalis in concentrated solutions; specifically, concentrated sodium hydroxide solution or concentrated potassium hydroxide solution;
[0037] Step 4: Coating: The porous tin is surface treated by a coating method to achieve doping and separation of the porous tin;
[0038] Among them, in step 4, the coating method is chemical vapor deposition (CVD) or polymer coating-carbonization; further, in step 4, when chemical vapor deposition (CVD) is used for coating, the carbon source of the chemical vapor deposition (CVD) method is one or more of methane, ethylene, ethane, and acetylene gases; the carrier gas is one or more of inert gases; specifically, helium or argon; and the reaction temperature is lower than the melting point of porous tin.
[0039] Example 2:
[0040] In this embodiment, during the actual production and processing, an aluminum-germanium-tin alloy is smelted, wherein the tin content is 95.3%, the germanium content is 3.5%, and the aluminum content is 1.2%; the purity of the raw metal should be greater than or equal to 99.99%; the alloy liquid temperature is 800°C, and the smelting protection gas is helium and hydrogen, wherein the hydrogen accounts for 2%; the smelted metal is gas atomized; the atomization pressure and the liquid flow rate are adjusted according to the powder particle size, and the powder particle size should be between 400-600nm; the atomization medium is helium and hydrogen, and the hydrogen The gas content is 2%; after the metal particles are cooled to room temperature, the alloy is etched with 1 mol / L hydrochloric acid for 12 hours at room temperature, and the material is then washed with water to remove the residual acid; porous tin is obtained after etching; the porous tin is coated; the coating method is chemical vapor deposition (CVD) to deposit carbon on the surface of the porous tin; the temperature is 650°C, the gas is methane, the carrier gas is argon and hydrogen, and the hydrogen content is 5%; the thickness of the coated carbon layer should be 5-20 nm; the coating thickness is achieved by adjusting the gas flow rate and pressure.
[0041] The properties of the materials prepared in Example 2 are shown in Table 1.
[0042]
[0043] Example 3:
[0044] In the actual production and processing process, the iron-cobalt-tin alloy is smelted, wherein the tin content is 95.7%, the iron content is 2.9%, and the cobalt content is 1.4%; the purity of the raw metal should be greater than or equal to 99.99%; the alloy liquid temperature is 1200℃, and the smelting protection gas is nitrogen and hydrogen, of which hydrogen accounts for 2%; the smelted metal is gas atomized; the atomization pressure and the liquid flow rate are adjusted according to the powder particle size, and the powder particle size should be between 400-600nm; the atomization medium is nitrogen and hydrogen, and hydrogen accounts for 2%. The ratio is 2%; after the metal particles are cooled to room temperature, the alloy is etched with 1 mol / L hydrochloric acid for 12 hours at room temperature, and the material is then washed with water to remove residual acid; porous tin is obtained after the etching is completed; the porous tin is coated; the coating method is to deposit carbon on the surface of the porous tin by chemical vapor deposition (CVD); the temperature is 650°C, the gas is ethane, and the carrier gas is argon and hydrogen, with a hydrogen content of 5%; the thickness of the coated carbon layer should be 5-20 nm; the coating thickness is achieved by adjusting the gas flow rate and pressure.
[0045] The properties of the materials prepared in Example 3 are shown in Table 2.
[0046]
[0047]
[0048] In summary, it must be said that compared with the existing hard carbon negative electrode for sodium ion batteries, the tin-based negative electrode has a higher energy density. At the same time, tin is more environmentally friendly; the present invention prepares a porous tin material by an alloy-etching method. Its innovation lies in that the material is obtained by an alloy of at least three metals. Tin provides the capacity of the battery negative electrode; aluminum is a pore-forming agent, which is removed by etching; germanium is an auxiliary metal to increase the melting point of the alloy to avoid melting or deformation of the porous material during the carbon coating process. (The melting point of tin is 231.9°C, and the temperature of carbon coating needs to be at least >600°C); the porous tin of the present invention can be mixed with a hard carbon negative electrode or used alone.
[0049] The three-dimensional porous material provided can prevent the material from pulverizing and breaking due to volume expansion. At the same time, the present invention isolates tin through coating, enhancing the structural stability of the porous tin and preventing material contact and self-aggregation. The three-dimensional porous structure of the porous tin gives it a higher specific surface area and a larger contact area with the electrolyte, thereby improving the efficiency of the electrochemical reaction. The carbon coating can enhance the cyclic stability of the porous tin and enhance the reliability and durability of the material. Compared with hard carbon, tin is more environmentally friendly and recyclable. It helps to reduce the environmental burden. By adding high-melting-point metals to form an alloy, the melting and deformation of the tin during the coating process is avoided.
[0050] The foregoing is merely a preferred embodiment of the present invention. It should be noted that those skilled in the art may make various improvements and modifications without departing from the principles of the present invention, and such improvements and modifications are also within the scope of protection of the present invention. Structures, devices, and operating methods not specifically described or explained herein shall, unless otherwise specified or limited, be implemented in accordance with conventional means in the art.
Claims
1. A method for preparing carbon-coated porous tin, characterized in that: The alloy is prepared by a gas atomization method, and then the porous tin is prepared by removing the auxiliary metal in the alloy. Finally, the porous tin is doped and separated by a hard carbon coating method to complete the preparation of the carbon-coated porous tin.
2. The method for preparing carbon-coated porous tin according to claim 1, characterized in that: The method for preparing the carbon-coated porous tin comprises the following specific steps: Step 1: Alloy smelting: the alloy is melted and mixed to obtain alloy liquid; Step 2: Granulation: The molten alloy is made into alloy particles in an atomizing tank by gas atomization; Step 3: Etching: removing at least one auxiliary metal in the alloy by etching to obtain porous tin or tin alloy; Step 4: Coating: The porous tin is surface treated by coating method to achieve doping and separation of the porous tin.
3. The method for preparing carbon-coated porous tin according to claim 2, characterized in that: In step 1, the alloy contains tin and at least one other auxiliary metal; the tin content is 80%-99%, and the auxiliary metal is one or more of antimony, germanium, copper, manganese, iron, cobalt, nickel, aluminum, silver, zinc, and tungsten; the purity of the raw metal is greater than or equal to 99.99%.
4. The method for preparing carbon-coated porous tin according to claim 3, characterized in that: In step 1: the smelting temperature is higher than the melting point of the alloy; the smelting protective atmosphere is hydrogen and one or more of helium, argon and nitrogen; the purity of a single gas is greater than 99.99%, and the proportion of hydrogen is less than or equal to 2%.
5. The method for preparing carbon-coated porous tin according to claim 2, characterized in that: In step 2, the atomizing gas is hydrogen and one or more of helium, argon, and nitrogen; the purity of a single gas is greater than 99.99%, and the proportion of hydrogen is less than or equal to 2%; the atomizing pressure is 1 MPa-10 MPa; and the median particle size D50 of the alloy material is 0.2-10 μm.
6. The method for preparing carbon-coated porous tin according to claim 2, characterized in that: The step 3 specifically involves removing at least one auxiliary metal in the alloy by one or more of acid, alkali or ion beam etching, sputtering etching, plasma etching, laser etching, electrochemical etching, and sandblasting etching methods to obtain porous tin or tin alloy.
7. The method for preparing carbon-coated porous tin according to claim 6, characterized in that: When the etching method adopts acid or alkali etching, the acid is one or more of strong acid solutions; the alkali is one or more of concentrated solution strong alkali.
8. The method for preparing carbon-coated porous tin according to claim 2, characterized in that: In the step 4, the coating method is a chemical vapor deposition CVD method or a polymer coating-carbonization method.
9. The method for preparing carbon-coated porous tin according to claim 8, characterized in that: In step 4, when chemical vapor deposition (CVD) is used for coating, the carbon source of the chemical vapor deposition (CVD) method is one or more of methane, ethylene, ethane, and acetylene gases; the carrier gas is one or more of inert gases; and the reaction temperature is lower than the melting point of porous tin.
Citation Information
Cited By
Preparation method and application of MXene / Sn composite material
CN120453340A
